2018
DOI: 10.1021/acsomega.7b01892
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxy-(Chloro)n-Boron Subnaphthalocyanines: Alloyed Mixture, Electron-Accepting Functionality, and Enhanced Solubility for Bulk Heterojunction Organic Photovoltaics

Abstract: The first set of phenoxy BsubNc compounds, PhO-Cl n BsubNc and F 5 -Cl n BsubNc, was synthesized through an axial displacement reaction of Cl-Cl n BsubNc with phenol and pentafluorophenol (respectively). Like their precursor, the products were found to be an alloyed mixture of phenoxylated Cl n BsubNcs with random positioning in the solid state yet consistent frequency of bay posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…When α‐6T was paired with the differently synthesized Cl‐Cl n BsubNcs (Figure ), it was discovered that higher degree of chlorination resulted in more efficient devices with PCE's ranging between 2.44 % and 4.32 % . Phenoxy‐BsubNc compounds (PhO‐Cl n BsubNc and F 5 ‐Cl n BsubNc, Figure b)) were synthesized in a subsequent study and also incorporated as electron acceptors in OPVs . A V OC exceeding 1.0 V was achieved in PHJ devices, but with less than half of the PCEs achieved for the commercial Cl‐Cl n BsubNc.…”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
“…When α‐6T was paired with the differently synthesized Cl‐Cl n BsubNcs (Figure ), it was discovered that higher degree of chlorination resulted in more efficient devices with PCE's ranging between 2.44 % and 4.32 % . Phenoxy‐BsubNc compounds (PhO‐Cl n BsubNc and F 5 ‐Cl n BsubNc, Figure b)) were synthesized in a subsequent study and also incorporated as electron acceptors in OPVs . A V OC exceeding 1.0 V was achieved in PHJ devices, but with less than half of the PCEs achieved for the commercial Cl‐Cl n BsubNc.…”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
“…The use of a planar heterojunction (PHJ) architecture limits the influence of morphology on device performance, making PHJ OPVs an ideal architecture to test material stability. Two similar classes of materials have been demonstrated to perform exceptionally well as electron-accepting fullerene replacements in laboratory-scale, planar heterojunction (PHJ) OPVs: boron subnaphthalocyanines (BsubNcs) and boron subphthalocyanines (BsubPcs). BsubNcs and BsubPcs have many synthetic handles for tuning performance, and synthetic procedures for achieving many different derivatives have already been demonstrated. ,, We recently determined that BsubNcs actually consist of an alloyed mixture of chlorinated species (Cl n BsubNc), a mixture that benefits their OPV performance . We also previously conducted small-scale outdoor tests on some BsubPc derivatives, determining that phenoxy and phenyl substituents in the axial position of a BsubPc significantly harm their outdoor stability relative to the prototypical Cl–BsubPc. , Cnops et al demonstrated a record power conversion efficiency of 8.4% for a PHJ OPV can be achieved by combining chloro–Cl n BsubNc (Cl–Cl n BsubNc) and chloro–BsubPc (Cl–BsubPc) with sexithiophene (α-6T) .…”
mentioning
confidence: 99%
“…Boron subnaphthalocyanines (BsubNcs, Figure 1) are a subgroup of the phthalocyanine macrocyclic family, which have attracted interest as functional organic semiconductors [1][2][3][4] and sensor materials [5] because of their synthetic tunability [6][7][8][9] and high thermal, chemical and photo-stability. [10][11][12] Structurally BsubNcs, and their counterparts boron subphthalocyanine (BsubPc), [13] differ from conventional metal-and metalloid-phthalocyanines (MPcs) [14] because of their molecular non-planar conformation and reduced trimeric ligand structure.…”
Section: Introductionmentioning
confidence: 99%
“…[4] It has also been shown that mixed alloyed composition remains constant on further chemical derivatization of Cl-ClnBsubNc and enables their integration into bulk-heterojunction OPVs. [9] In contrast with the developments in OPVs, far fewer reports exist on the applications of BsubPcs showing a mixture of host (Alq3) and guest emission, with a peak EQE 0.41% . [34] Given the potential of Cl-ClnBsubNc as light emitting materials, we wish to understand the influence on the degree of bay-position chlorination on their luminescence properties.…”
Section: Introductionmentioning
confidence: 99%